Proporsi kejadian depresi pada lansia di wilayah kerja Puskesmas Karangasem I, Bali-Indonesia - I Gst. Agung Yudha Prasetya; Ni Luh Putu Aryastuti (Intisari Sains Medis, 2019)
Introduction: Indonesia entered an ageing population era because the geriatrics percentage was above 7%. In 2015, Karangasem I Community Health Centre served 3015 geriatrics. The escalation of chronic disease visits at geriatric polyclinic indicated an increasing geriatrics health burden. Depression was one of the most frequent psychiatric problems on geriatrics. In the preliminary survey were found that 3, out of 10 geriatrics had depressive mood. This study aimed to found the proportion of depression among geriatrics and the possible factors associated at Karangasem I Community Health Centre Region.Method: This was a descriptive cross sectional study. Pertima Village was randomly chosen and 73 samples were obtained using accidental sampling technique. Geriatric Depression Scale-15 was used to determine depression.Result: The result showed the proportion of depression was 67,1% with 57,1% was mild depression. The tendency of depression was found on several factors such as being female (67,4%), age category â‰¥80 years old (88,9%), unemployed (69,4%), uneducated (83,3%), widow/widower/single status (69,4%), living alone (76,9%), being the head of household (72,7%), having chronic disease (68%), and never participate on posyandu (100%).Conclusion: Prevalence of geriatric depression are quite high, sosial participation is needed to assist in preventing depression on geriatrics. Therefore, role of Community Health Centre was necessary on planning and holding more program and activities for elderly. Besides, it was necessary in improving the medical personnel skill on psychiatry for early detection and prompt treatment of depression among elderly.